Economical 3D-Printed Robotic Arm for Educational Training Purpose - Hadisujoto, Budi; Budiarta, Wahyu Nur; Frandito, Raffy; Saptaji, Kushendarsyah; Triawan, Farid; Wibowo, Djati; Ong, Janice (Jurnal Teknologi, 2025)
The advancement of Engineering technology requires universities as the frontier to educate engineering students with the latest skillset. Fast progress of Artificial Intelligence (AI) shown by the recently released of open AI such as ChatGPT, Genius, etc., has opened a new trend of technological tools. Hence, it is necessary or it can be said a must to train future engineers how to at least use these tools. Robotics and automation have long been used to assist humans in manufacture, logistic, health, and many other areas. Implementing AI into robotics creates intelligent systems which are predicted to be widely used. However, for educational institutions, especially in developing countries, the cost to afford the training robot equipment is still pricy. Here, we present designing and building of an economical robotic arm using 3D printed parts and open sources. The robot arm has six Degrees of Freedoms (DoF) and capable of lifting about 450 grams of maximum load. Some suggestions include future development are presented.